Podcasting in English Classroom? Why Not? - Made Hery Santosa (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2008)
The present paper aims at discussing the use of podcast as one of online media delivery inEnglish instruction. Advanced ICT development has provided its users both challenges andopportunity where it creates a strong demand to utilize of ICT in classroom teaching. One of the waysthat can be applied to enhance with the technology use in a situated multi-learning environment usingICT systems is the use of podcast. By podcast, teaching English can be conducted in advanced waysby the use of online media delivery. There are several benefits that students can get from podcast,namely 1) it gives students a potential audience of thousands for their work, 2) it is great fordeveloping literacy skills, 3) podcasts can be interactive, and 4) making a podcast is also great fordeveloping teamwork skills. Especially in the teaching of English, podcasting will help the studentsimprove their communication skills as well as their creativity in making a radio show will increase.Kata kunci: ICT, podcasting, English instruction.